2014
DOI: 10.1002/jemt.22421
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light curing units and fluoride mouthrinse on morphological surface and color stability of a nanofilled composite resin

Abstract: Composite resin is a dental material susceptible to color change over time which limits the longevity of restorations made with this material. The influence of light curing units and different fluoride mouthrinses on superficial morphology and color stability of a nanofilled composite resin was evaluated. Specimens (N = 150) were prepared and polished. The experimental groups were divided according to the type of light source (halogen and LED) and immersion media (artificial saliva, 0.05% sodium fluoride solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(71 reference statements)
0
6
0
6
Order By: Relevance
“…Todos os grupos avaliados tiveram ΔE maior que 1,0 e menor que 3,0, significando alterações perceptíveis, mas clinicamente aceitáveis 5,6,10,18,21,22 . Os valores de ΔE foram maiores para as amostras imersas em Coca-Cola  e estatisticamente significantes para as resinas fotopolimerizadas por QTH e LED 2 (p = 0,01).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Todos os grupos avaliados tiveram ΔE maior que 1,0 e menor que 3,0, significando alterações perceptíveis, mas clinicamente aceitáveis 5,6,10,18,21,22 . Os valores de ΔE foram maiores para as amostras imersas em Coca-Cola  e estatisticamente significantes para as resinas fotopolimerizadas por QTH e LED 2 (p = 0,01).…”
Section: Discussionunclassified
“…De modo geral, a composição do material, o tipo de sistema fotoiniciador e a taxa de conversão desempenham um papel importante para a estabilidade da cor das resinas 18,21 . Oliveira et al 10 testaram a estabilidade de cor da resina nanoparticulada Filtek Z350 XT em solução ácida e notaram efeito deletério do material devido ao amolecimento da matriz resinosa, que pode promover a sua degradação, aumentando a suscetibilidade ao manchamento. A taxa de calor emitida por uma unidade de polimerização também pode interferir nas propriedades da resina.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The extent of resin cure is affected mainly by monomer and activator type, light source intensity, duration of exposure and filler type and size (27). According to SEM observations, some authors have demonstrated that different curing units did not influence the superficial morphology of composite resins (28). Even if no morphology alteration has been reported, it has been shown that postcuring oven treatment increased the surface microhardness of composites (29).…”
Section: Discussionmentioning
confidence: 99%